In Situ Coupling Strategy for Anchoring Monodisperse Co9S8 Nanoparticles on S and N Dual-Doped Graphene as a Bifunctional Electrocatalyst for Rechargeable Zn–Air Battery - Shao, Qi; Liu, Jiaqi; Wu, Qiong; Li, Qiang; Wang, Heng‑guo; Li, Yanhui; Duan, Qian (Nano-Micro Letters, 2019)
An in situ coupling strategy to prepare Co9S8/S and N dual-doped graphene composite (Co9S8/NSG) has been proposed. The key point of this strategy is the function-oriented design of organic compounds. Herein, cobalt porphyrin derivatives with sulfo groups are employed as not only the coupling agents to form and anchor Co9S8 on the graphene in situ, but also the heteroatom-doped agent to generate S and N dual-doped graphene. The tight coupling of multiple active sites endows the composite materials with fast electrochemical kinetics and excellent stability for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The obtained electrocatalyst exhibits better activity parameter (ΔE = 0.82 V) and smaller Tafel slope (47.7 mV dec−1 for ORR and 69.2 mV dec−1 for OER) than commercially available Pt/C and RuO2. Most importantly, as electrocatalyst for rechargeable Zn–air battery, Co9S8/NSG displays low charge–discharge voltage gap and outstanding long-term cycle stability over 138 h compared to Pt/C–RuO2. To further broaden its application scope, a homemade all-solid-state Zn–air battery is also prepared, which displays good charge–discharge performance and cycle performance. The function-oriented design of N4-metallomacrocycle derivatives might open new avenues to strategic construction of high-performance and long-life multifunctional electrocatalysts for wider electrochemical energy applications. Highlights: 1 An effective in situ coupling strategy is proposed to construct Co9S8 nanoparticles/doped graphene. 2 Cobalt porphyrin derivative is employed as both coupling and heteroatom-doped agents. 3 The bifunctional oxygen electrocatalyst finds application in rechargeable all-solid-state Zn–air batteries.